2009
DOI: 10.1099/mic.0.030148-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rv3852 as a nucleoid-associated protein in Mycobacterium tuberculosis

Abstract: Tuberculosis remains the major cause of mortality due to a bacterial pathogen, Mycobacterium tuberculosis. The molecular mechanisms of infection and persistence have not been completely elucidated for this pathogen. Studies involving nucleoid-associated proteins (NAPs), which have been related to the control and influence of virulence genes in pathogenic bacteria, can help unveil the virulence process of M. tuberculosis. Here, we describe the initial characterization of an ORF for an M. tuberculosis putative N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…The protein bound to DNA in a sequence-independent manner, and with increasing protein concentrations, the DNA-protein complexes were increased. At higher concentrations (75 to 100 nM) of the protein, the DNA-protein complexes failed to enter the gel, suggesting the formation of higher-order oligomeric DNA-protein structures, as reported previously (28). These structures presumably formed due to the cooperative binding of the protein on DNA.…”
Section: Resultsmentioning
confidence: 66%
“…The protein bound to DNA in a sequence-independent manner, and with increasing protein concentrations, the DNA-protein complexes were increased. At higher concentrations (75 to 100 nM) of the protein, the DNA-protein complexes failed to enter the gel, suggesting the formation of higher-order oligomeric DNA-protein structures, as reported previously (28). These structures presumably formed due to the cooperative binding of the protein on DNA.…”
Section: Resultsmentioning
confidence: 66%
“…Together, this suggests that EspR and Lsr2 may control gene expression, including that of many cell wall functions, in a divergent manner with EspR possibly replacing Lsr2 at certain sites and vice-versa. It is striking that in all sequenced mycobacterial genomes espR is very close to the hns gene encoding another NAP [33] and this may also indicate functional interplay. These hypotheses can be tested experimentally by using the corresponding antibodies to perform ChIP-Seq experiments on Mtb strains at different stages in the growth cycle to localize their binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…Since Rv3852 had been hypothesized to play a role as a NAP (19), thus contributing to shaping the chromosome, the MICs of drugs that have an effect on the topology of DNA were measured (28). We used the fluoroquinolones moxifloxacin and novobiocin targeting the GyrA and GyrB subunits of DNA gyrase, respectively, for this purpose together with rifampin, inhibiting RNA synthesis, as a control.…”
Section: Resultsmentioning
confidence: 99%
“…Curiously, Werlang and colleagues reported that M. tuberculosis Rv3852 does not complement hns mutations in E. coli (19), whereas Lsr2, another NAP, does (20) and is therefore a functional homologue of E. coli H-NS. Ectopic expression of M. tuberculosis rv3852 in M. smegmatis led to a less-compacted nucleoid, altered biofilm formation, and decreased sliding motility (21).…”
Section: Abstract Tuberculosis Mycobacterium Tuberculosis H-ns Napmentioning
confidence: 99%